The Influence of Culture Implementation and Maturity Level on OHS Performance in The Upholstery Oil and Gas Company Citic Seram Energy Limited - Rohman YUDIAWAN; Fauziah EDDYONO; Marlinda Irwanti POERNOMO (International Journal of Environmental, Sustainability, and Social Science, 2025)
The upstream oil and gas industry is inherently associated with a high level of Occupational Health and Safety (OHS) risks, in which two critical determinants of effective risk management are safety culture and its maturity level. Safety culture encompasses the values, attitudes, and behaviors demonstrated by an organization toward safety, whereas safety culture maturity reflects the extent to which such values are systematically institutionalized and sustained. The novelty of this study lies in highlighting the importance of developing safety culture beyond formal implementation, with particular emphasis on advancing maturity toward proactive and generative levels. Accordingly, this research aims to examine the influence of safety culture implementation and safety culture maturity on safety performance at Citic Seram Energy Limited. Employing a quantitative design, data were collected through a purposive sample of 80 respondents using a Likert-scale questionnaire and subsequently analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The empirical results demonstrate that safety culture exerts a positive and statistically significant effect on safety performance (β = 0.45; p < 0.001), while safety culture maturity also exhibits a positive and significant effect (β= 0.38; p < 0.01). Collectively, these variables account for 62% of the variance in safety performance. In conclusion, the findings underscore that strengthening safety culture and enhancing its maturity are essential strategies for significantly improving safety performance within the upstream oil and gas sector.